2012
DOI: 10.3399/bjgp12x658269
|View full text |Cite
|
Sign up to set email alerts
|

Telehealthcare for chronic obstructive pulmonary disease: Cochrane Review and meta-analysis

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is common. Telehealthcare, involving personalised health care over a distance, is seen as having the potential to improve care for people with COPD. AimTo systematically review the effectiveness of telehealthcare interventions in COPD to improve clinical and process outcomes. Design and settingCochrane Systematic Review of randomised controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
176
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(187 citation statements)
references
References 26 publications
8
176
0
3
Order By: Relevance
“…Despite these encouraging results, the penetration of these technological advances in the clinical practice is still slow, especially when compared with other respiratory chronic diseases or others pathologies [98,99,[101][102][103]. Furthermore recently published results questioned the validity of this technology as a method to delivery healthcare for all populations [104].…”
Section: Role Of Tele-monitoring In Sleep-related Breathing Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these encouraging results, the penetration of these technological advances in the clinical practice is still slow, especially when compared with other respiratory chronic diseases or others pathologies [98,99,[101][102][103]. Furthermore recently published results questioned the validity of this technology as a method to delivery healthcare for all populations [104].…”
Section: Role Of Tele-monitoring In Sleep-related Breathing Disordersmentioning
confidence: 99%
“…For example, in many cases one night and follow-up visits in the sleep laboratory are not enough to adequately set the ventilator, ICT can support the home refinement of the titration of these patients [98]. Tele-consultations can also positively contribute to OSA management [99]. A recent multicentre randomised controlled trial provided evidence that a strategy based on a web platform and tele-consultations, for the CPAP follow-up of OSA patients is as effective as the face-to-face approach at lower costs [87].…”
Section: Role Of Tele-monitoring In Sleep-related Breathing Disordersmentioning
confidence: 99%
“…Therefore, innovative interventions aimed to reduce the burden to our system (e.g., reduce hospitalization) would be beneficial. An example of such interventions is remote patient monitoring (RPM) which aims to provide the ''appropriate care at the appropriate time and place in the most appropriate manner'' [1], focusing on better disease management [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the management of chronic conditions, telemedicine has been associated with fewer ED attendances, a reduction of hospital admissions and lower health costs (Purdy, 2010;McLean et al, 2012;Steventons et al, 2012;Bashur et al, 2014). A three-year randomised controlled trial in England showed positive results associated with the use of telemedicine on patients with long-term conditions including diabetes, chronic obstructive pulmonary disease (COPD) and heart failure.…”
mentioning
confidence: 99%